Biomimetic polymeric semiconductor based hybrid nanosystems for artificial photosynthesis towards solar fuels generation via CO2 reduction. (July 2016) - Zhou, Han; Li, Peng; Liu, Jian; Chen, Zupeng; Liu, Lequan; Dontsova, Dariya; Yan, Runyu; Fan, Tongxiang; Zhang, Di; Ye, Jinhua
Abstract: In photosynthesis, an intricate polymeric system is constructed by connecting a light-harvesting antenna network, a molecular water oxidation center, and CO2 or proton-reduction machinery in a nanolayered architecture as a basic photosynthetic unit for solar-to-fuels conversion. Herein, we present a prototype basic artificial photosynthetic unit by connecting a typical CO2 /proton reduction catalyst, a cocatalyst and an electron mediator as well as CO2 activator into a polymer based nano-architectured system for artificial photosynthesis with water and CO2 . Here, g-C3 N4 nanosheets, mimicking the nanolayered thylakoids stacks are demonstrated as promising photocatalytic elements with planar configuration and high surface area, which provide an excellent platform for the assembly of other analogous elements. Au NPs are served as a suitable cocatalyst. ZIF-9, as a typical cofactor to illustrate this concept here, is used as a CO2 concentrator and an electron mediator to promote the redox reaction. In artificial photosynthesis, driven by light energy, water and CO2 are served electron donor and carbon source respectively for the generation of H2 and CO. The artificial unit described here as a simple model, provides an important biomimetic step down a path aligned with the low-cost artificial photosynthetic systems manufacturing. Graphical abstract: Highlights: A typical CO2 reduction catalyst, a cocatalyst and an electron mediator/CO2 activator are connected into nano-architectured system for artificial photosynthesis. g-C3 N4 nanosheets, mimicking the nanolayered thylakoids stacks are demonstrated as promising photocatalytic elements which provide platforms for the assembly of other analogous elements. ZIF-9, as a typical cofactor is used as a CO2 concentrator and an electron mediator to promote the redox reaction. In artificial photosynthesis, driven by light energy, water and CO2 are served an electron donor and carbon source respectively to generate solar fuels.